Relation between the bronchial obstructive response to inhaled lipopolysaccharide and bronchial responsiveness to histamine. - Michel, O (1992)
BACKGROUND: Bronchoconstriction has developed after inhalation of lipopolysaccharide in a dose of 20 micrograms in asthmatic patients and of 200 micrograms in normal subjects. This study set out to determine whether the bronchial response to lipopolysaccharide was related to non-specific bronchial responsiveness and atopy. METHODS: Sixteen subjects with a fall in specific airway conductance of 40% (PD40sGaw) after inhaling up to 900 micrograms histamine inhaled 20 micrograms lipopolysaccharide (from Escherichia coli type 026:B6) a week after bronchial challenge with a control solution of saline. The bronchial response over five hours was measured as change in FEV1 and area under the FEV1-time curve. RESULTS: FEV1 fell significantly more after lipopolysaccharide than after diluent inhalation, the difference in mean (SE) FEV1 being 4.6% (5.4%); response was maximal 60 minutes after lipopolysaccharide inhalation and lasted more than five hours. Histamine PD20FEV1 and PD40sGaw correlated with the fall in FEV1 after lipopolysaccharide inhalation. There was no difference in the proportions of responders and non-responders to lipopolysaccharide who were atopic. CONCLUSION: Lipopolysaccharide induced bronchial obstruction is associated with non-specific responsiveness but not with atopy.